2009
DOI: 10.1146/annurev.clinpsy.032408.153607
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Tobacco Use: Evidence from Societal and Community Influences on Tobacco Use and Dependence

Abstract: There is little doubt that nicotine addiction sustains tobacco use in most people and that individual variation in response to tobacco has a strong biological basis. However, the great diversity in tobacco use behaviors observed between countries and within countries over time suggests that biology alone cannot fully explain these variations. This review examines the role of the social environment in understanding tobacco use behaviors and efforts to curb tobacco use at the population level. We conclude that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 122 publications
0
23
0
1
Order By: Relevance
“…This means that there may need to be renewed focus on treatments that help smokers address their biological dependence to nicotine. Normal volitional factors seem to be sufficient to motivate attempts, and these need to be supported and enhanced, but unless we are prepared to accept low quit rates, there is a need to develop more effective interventions to help smokers remain smoke free (Cummings, Fong, & Borland, 2009). Motivation is a complex set of beliefs and inclinations that we don't know enough about, especially postquitting.…”
Section: Core Predictor Variablementioning
confidence: 99%
“…This means that there may need to be renewed focus on treatments that help smokers address their biological dependence to nicotine. Normal volitional factors seem to be sufficient to motivate attempts, and these need to be supported and enhanced, but unless we are prepared to accept low quit rates, there is a need to develop more effective interventions to help smokers remain smoke free (Cummings, Fong, & Borland, 2009). Motivation is a complex set of beliefs and inclinations that we don't know enough about, especially postquitting.…”
Section: Core Predictor Variablementioning
confidence: 99%
“…A recent report from the Substance Abuse and Mental Health Services Administration found that the prevalence of smoking in the United States declined from 1997 to 2011 among those without, but not with, mental illness (Center for Behavioral Health Statistics and Quality, 2013). Further, persons with serious mental illness are at increased risk for tobacco-related illnesses and die, on average, 25 years prematurely (Colton & Manderscheid, 2006). This issue is particularly relevant from a tobacco control perspective, given evidence that one third to one half of cigarette smokers have a comorbid diagnosis (Grant, Hasin, et al, 2004;Lasser et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Tobacco control policies, such as smoke-free air laws, have been demonstrated to effectively reduce smoking rates in the general population (see Cummings, Fong, & Borland, 2009, for a review). To date, 28 states have implemented statewide smoke-free air laws in restaurants and bars (American Advance Access publication February 24, 2014…”
Section: Methodsmentioning
confidence: 99%
“…[6,7] Although there is no doubt that nicotine addiction contributes to the difficulty of smoking cessation, [5] the smoker's social context also plays a role. [8,9] Various studies have shown how the social environment affects smoking behaviours, including a relationship between the decrease in cigarettes smoked in western societies and increased awareness of the dangers of tobacco use, the socioeconomic status, [8] the changing social norms, and governmental actions to regulate tobacco use, the sale of cigarettes, and warning labels on cigarette packaging. [10] On the other hand, researchers have described interpersonal factors that may contribute to an individual's success or failure in quitting smoking.…”
Section: Introductionmentioning
confidence: 99%